ANALISIS DEIKSIS DALAM NOVEL “SKAYA AND THE BIG BOSS” KARYA MARSELLA TINA: PERSPEKTIF PRAGMATIK GEORGE YULLE - Hasun, Moh; Hodairiyah; Asmoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the types of deixis and thoroughly analyze the intended meaning of utterances within the dialogue of the novel *Skaya and The Big Boss* by Marsella Tina, utilizing George Yule’s pragmatic framework. The research employs a qualitative descriptive approach, specifically a library-based case study method. The data focuses on character-to-character utterances containing elements of personal, spatial (place), and temporal (time) deixis. Data collection utilized library research techniques integrated with listening methods, specifically the basic "read-and-listen" technique and the advanced "note-taking" technique. Subsequently, data analysis applied the distributional method, operationalized through the basic "Immediate Constituent Analysis" (BUL) technique and the advanced "deletion" technique. The results indicate that personal deixis (first, second, and third person) dominates the dialogue throughout the novel. Specifically, the data identified includes 2,540 instances of personal deixis, 475 of spatial deixis, and 192 of temporal deixis. Application of the deletion technique revealed that the omission of deictic words leads to critical ambiguity regarding referential information for the reader. Thus, an understanding of the pragmatic context is essential for grasping the full meaning and underlying intent behind the novel's dialogues.